THE EFFECTIVENESS OF QUR'AN CULTURE IN IMPROVING THE QUALITY OF QUR'AN READING IN STUDENTS MAS AL WASHLIYAH 22 TEMBUNG - Dwi Afri Yani; As’ad (International Journal of Cultural and Social Science, 2025)
In the current generation of young people, someone who cannot read and understand the Qur'an is a problem. This study aims to examine the effectiveness of the Qira'atul Qur'an culture in improving the quality of Al-Qur'an reading in students of MAS Al Washliyah 22 Tembung. Qualitative research uses a field approach or (field research). Qualitative research is conducted by collecting data through observation, interviews and documentation. Furthermore, using data analysis techniques by collecting data, reducing data, presenting data and drawing conclusions. The results of the study indicate that the Qira'atul Qur'an culture implemented through routine activities of reading and memorizing the Qur'an is effective in improving the quality of student reading. This study recommends the implementation of the Qira'atul Qur'an culture as an effective strategy in improving the quality of Al-Qur'an reading in educational institutions, by paying attention to teaching methods, teacher support, student motivation, and a supportive social environment.